Hoya pyrifolia (Apocynaceae), a new species from south-western Yunnan, China - Huang, Er-Feng (PhytoKeys, 2021)
Hoya pyrifolia, a new species of Apocynaceae from Yunnan Province, China, is described and illustrated. Results from phylogenetic analyses, based on combined DNA fragments of the nuclear ribosomal external transcribed spacer (ETS), intergeneric transcribed spacer (ITS) and three plastid DNA fragments (matK, psbA-trnH and trnT-trnL), showed that the new species was nested within a clade, including Hoya species distributed in the subtropical foothills of the Himalayas and the Tibet-Sichuan Plateau. Morphologically, the new species can be distinguished from its close relatives by its pyriform and slightly pubescent leaves, as well as the 4-flowered inflorescences.